ANALISIS HUKUM ISLAM TERHADAP FATWA MAJELIS ULAMA INDONESIA NOMOR 02/MUNAS-VIII/MUI/2010 TENTANG NIKAH WISATA - Eriskha Nur Subihatin Nisa’; Khoirul Asfiyak; Moh. Muslim (Jurnal Hikmatina, 2021)
Humans are social creatures who have in common to live in pairs between men and women. Marriage is the inner and outer bond between men and women as husband and wife, and the purpose is to establish a happy and eternal family based on Almighty God, as stated in Article 1 of the law. RI. Law No. 1 of 1974 on Marriage. With regard to marriage in Indonesia, marriages still exist between foreign Muslims and indigenous Muslim women who are married in accordance with current regulations. This is the reason to analyze the practice of tourist marriages that occur and to find out how the MUI fatwa on tourist marriages is from the perspective of Islamic law. This research was conducted by reviewing the MUI fatwa No 02/MunasVIII/MUI/2010  tourist marriages, to find out how MUI stilpulates fatwa, as well as an understanding of the community towards the law of marriage. The method used in this study is library research, and its nature is to use deductive thinking methods for descriptive analysis. And the result of this research is a form of mut’ah marriage which is haram and this is included in the category of new problems because the discussion is not found in classical fiqh book. Keywords: Analysis, Fatwa, and Marriage Tourism